Odpowiedzi

2010-02-25T20:31:57+01:00
A)
2a² +7=a(1+2a)
2a²+7=a+2a²
2a²-2a²-a=-7
-a=-7
a=7

b)
3a(a-1)=a(3a-2)
3a²-3a=3a²-2a
3a²-3a²+2a+3a
5a
ten przykład jest dobrze przez Ciebie napisany
c)
2a-a²+a(2+a)=a+18
2a-a²+2a+a²=a-18
2a-a²+2a+a²-a=-18
3a=-18
a=-6

d)
a²+5=5a(0,2a+3)
a²+5=a²+15a
a²-a²-15a=-5
-15a=-5
a=⅓
7 3 7
2010-02-25T20:34:06+01:00
A)
2a^2 +7=a(1+2a)
2a^2+7=a+2a^
a=7

b) 3a(a-1)=a(3a-2)
3a^2-3=3a^2-2a
2a=3\:2
a= 1i1/2

c)2a-a^2+a(2+a)=a+18
3a=18\:3
a=6

d) a^2+5=5a(0,2a+3)
a^2+5=a^2+15a\:15
a= 1/3

3 3 3